New oral anticoagulants in elderly patients with atrial fibrillation - Deedwania, Prakash C (The American journal of medicine, 2013)
The prevalence of atrial fibrillation increases with age, augmenting the risk of embolic stroke in elderly individuals. Clinical practice guidelines recommend the long-term use of oral anticoagulation in elderly patients with atrial fibrillation to reduce risk of stroke. Until recently, vitamin K antagonists (eg, warfarin) were the only oral anticoagulants available, but using warfarin in elderly patients can be challenging. Newer oral anticoagulants may offer specific benefits and increased convenience for elderly patients, because they have predictable pharmacologic profiles, a rapid onset of action, a wide therapeutic window, no requirement for routine coagulation monitoring, and fewer and better-defined food and drug interactions compared with warfarin. This review highlights the benefits and challenges of warfarin use in elderly patients with atrial fibrillation and discusses potential efficacy and safety benefits for newer oral agents in these patients. The potential for increased rates of major bleeding in the elderly, particularly those with numerous concomitant medications or renal impairment, also is discussed. Practical considerations for the use of long-term anticoagulation in elderly patients also are discussed.